1997
DOI: 10.1590/s0104-42301997000400006
|View full text |Cite
|
Sign up to set email alerts
|

Vasculite urticariforme hipocomplementêmica como primeira manifestação do lúpus eritematoso sistêmico

Abstract: RESUMO -A síndrome vasculite urticariforme hipocomplementêmica é uma vasculite leucocitoclástica que se apresenta com lesões urticariformes, associada a febre, artralgias, artrite e cólica abdominal. Outras manifestações sistê-micas incluem a presença de glomerulonefrite, uveíte, episclerite, doença pulmonar obstrutiva e alterações neurológicas. Alguns casos associados ao lúpus eritematoso sistêmico (LES) (USP) em março de 1988, com história de lesões eritemato-pruriginosas e dolorosas em placas de início … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Our patient showed 1) photosensitivity; 2) arthritis involving more than two peripheral joints; 3) immunologic disorder (IgG and IgM anticardiolipin, anti-RNP and anti-Ro antibodies); 4) antinuclear antibody in the absence of drug use; in addition to neurological disorders (aseptic meningitis and transverse myelitis) 1,8,11 , and the chronic urticaria 7 . Brey et al (2002) found neuropsychiatric syndromes associated with SLE (NPSLE) in 80% of 128 patients 10 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our patient showed 1) photosensitivity; 2) arthritis involving more than two peripheral joints; 3) immunologic disorder (IgG and IgM anticardiolipin, anti-RNP and anti-Ro antibodies); 4) antinuclear antibody in the absence of drug use; in addition to neurological disorders (aseptic meningitis and transverse myelitis) 1,8,11 , and the chronic urticaria 7 . Brey et al (2002) found neuropsychiatric syndromes associated with SLE (NPSLE) in 80% of 128 patients 10 .…”
Section: Discussionmentioning
confidence: 69%
“…In fact, she presented skin lesions aggravated by sunlight and lasting more than 36 hours, in addition to aseptic meningitis and anti-Ro (SS-A) antibodies positive, suggesting the presence of UV 4,7 . However, differing from this case, in SS occurs enlargement of FIGURA 4.…”
Section: Discussionmentioning
confidence: 99%